Molecular Characterization of Human Atypical Sorbitol-Fermenting Enteropathogenic Escherichia coli O157 Reveals High Diversity - Kossow, Annelene (J Clin Microbiol, 2016)
Alongside the well-characterized enterohemorrhagic Escherichia coli (EHEC) O157:H7, serogroup O157 comprises sorbitol-fermenting typical and atypical enteropathogenic E. coli (EPEC/aEPEC) strains that carry the intimin-encoding gene eae but not Shiga toxin-encoding genes (stx). Since little is known about these pathogens, we characterized 30 clinical isolates from patients with hemolytic uremic syndrome (HUS) or uncomplicated diarrhea with respect to their flagellin gene (fliC) type and multilocus sequence type (MLST). Moreover, we applied whole-genome sequencing (WGS) to determine the phylogenetic relationship with other eae-positive EHEC serotypes and the composition of the rfbO157 region. fliC typing resulted in five fliC types (H7, H16, H34, H39, and H45). Isolates of each fliC type shared a unique ST. In comparison to the 42 HUS-associated E. coli (HUSEC) strains, only the stx-negative isolates with fliCH7 shared their ST with EHEC O157:H7/H(−) strains. With the exception of one O157:H(−)(fliCH16) isolate, HUS was exclusively associated with fliCH7. WGS corroborated the separation of the fliCH7 isolates, which were closely related to the EHEC O157:H7/H(−) isolates, and the diverse group of isolates exhibiting different fliC types, indicating independent evolution of the different serotypes. This was also supported by the heterogeneity within the rfbO157 region that exhibited extensive recombinations. The genotypic subtypes and distribution of clinical symptoms suggested that the stx-negative O157 strains with fliCH7 were originally EHEC strains that lost stx. The remaining isolates form a distinct and diverse group of atypical EPEC isolates that do not possess the full spectrum of virulence genes, underlining the importance of identifying the H antigen for clinical risk assessment.